Staging the Audio Describer: An Exploration of Integrated Audio Description - Louise Fryer (Disability Studies Quarterly, 2018)
This article explores the phenomenon of integrated audio description (AD) and the ways in which access provision for blind people can be embedded into the creative process. Exploring a practical example where a describer became a character within a production staged by a company of blind and partially blind actors, it compares an approach to AD that is open and collaborative with traditional closed approaches, where the AD is delivered by an external interpreter. The consequences for the authenticity of the access and the language of the AD are also discussed in order to explore how tense, timing and flexibility distinguish AD from stage directions.